Temporal trend and factors associated with spatial distribution of congenital syphilis in Brazil: An ecological study - Dantas, Janmilli da Costa; Marinho, Cristiane da Silva Ramos; Pinheiro, Yago Tavares; Ferreira, Maria Ângela Fernandes; da Silva, Richardson Augusto Rosendo (Frontiers in Pediatrics, 2023)
Objective: This study analyzed the temporal trend and spatial distribution of CS in Brazil from 2008 to 2018 and identified spatial correlations with socioeconomic and prenatal care factors. Methods: We assessed spatial correlations between the incidence of CS and socioeconomic conditions and access to prenatal care. This ecological study conducted a time series analysis in Brazil and spatial analysis in 482 Immediate Regions of Urban Articulation (RUAs). We included cases of CS reported in the Notifiable Diseases Information System and the Live Birth Information System from January 1, 2008, to December 31, 2018. Socioeconomic conditions (percentage of individuals with inadequate water supply and sanitation) were extracted from the 2010 census, whereas the Live Birth Information System provided data on access to prenatal care (percentage of live births with 1 to 3 prenatal care appointments). The Joinpoint Regression software performed the temporal trend analysis, while the GeoDa software assessed territorial clusters using the Moran’s I and Local Spatial Association Indicator. Results: The incidence of CS showed an upward trend (annual percent change [APC] 1 = 263.2; 95% CI: 151.1 to 425.4 [APC] 1=26.96; 95%CI: 18.2 to 36.3; APC 2=10.25; 95%CI: 2.7 to 28.4) and was unevenly distributed across RUAs in Brazil (Moran’s I=0.264, p≤0.05). It also presented a direct spatial correlation with the percentage of individuals with inadequate water supply and sanitation (Moran’s I = 0.02, p≤0.05) and the percentage of live births with 1 to 3 prenatal care appointments (Moran’s I = 0.03, p≤0.05). Conclusion: We found a growth trend of CS in Brazil between 2008 and 2018. Moreover, inequalities in socioeconomic conditions and access to prenatal care influenced the spatial distribution of this disease.